Sociocultural perceptions of suicide in Pakistan: A systematic review & qualitative evidence synthesis - Ahsan Mashhood; Gul Saeed; Fatima Sami (SSM - Mental Health)
Suicide remains a significant public health issue in Pakistan, where social stigma and religious prohibitions create formidable barriers to understanding and intervention. Despite its recent decriminalization, the broader socio-cultural perceptions of suicide remain largely unexplored. Guided by the socio-ecological framework, this qualitative evidence synthesis examines how non-terrorist suicide is perceived across individual, familial, community, and institutional layers in Pakistan. A systematic review was conducted of over six databases up until July 2024 (PsycINFO, PubMed, EBSCO, Web of Science, ProQuest Premium, SCOPUS) and pearling through grey literature (AKU eCommons, QAU repository, Google Scholar). A total of eight studies (out of 1923) met the inclusion criteria. Thematic analysis of qualitative literature identified five key dimensions shaping these perceptions. At the individual level, suicide is often attributed to supernatural influences, mental illness, or a lack of resilience; familial dynamics prioritize ‘izzat’ over individual well-being enforcing invisibility; gendered perceptions of shame and honour further restrict women's access to help; cultural and religious prohibitions, such as labeling suicide the “ultimate sin,” further amplify ostracism and inhibit discussions about mental health; structural neglect, characterized by inadequate resources and societal dismissal, perpetuates stigma and inhibits systemic change. These findings are contextualized within Pakistan's unique religo-legal and socio-cultural dynamics. Our policy recommendations include incorporating mental health education into school curricula, community-based initiatives to challenge harmful norms, and establishing accessible mental health services for local needs.